2011
DOI: 10.1007/s12282-011-0265-6
|View full text |Cite
|
Sign up to set email alerts
|

Among triple-negative breast cancers, HER2(0) breast cancer shows a strong tendency to be basal-like compared with HER2(1+) breast cancer: preliminary results

Abstract: In TNBC, HER2(0) breast cancer showed a strong tendency to include more of the basal-like phenotype compared with HER2(1+) breast cancer. The staining results indicated the possibility that HER2(0) breast cancer and HER2(1+) breast cancer have different characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Compared with the non-anthracycline drugs, hER2-positive breast cancer is more sensitive to the treatment of anthracycline-containing drugs. however, recent clinical studies have shown that, in fact, the predictive value of the efficacy of anthracycline drugs on HER2-positive breast cancer may be affectd by the synergistic amplification of the TOP2A gene (19). The TOP2A gene is adjacent to the hER2 gene, located in the 21 site of the long arm of chromosome 17, which is expressed as amplification or deletion in breast cancer with HER2 gene amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the non-anthracycline drugs, hER2-positive breast cancer is more sensitive to the treatment of anthracycline-containing drugs. however, recent clinical studies have shown that, in fact, the predictive value of the efficacy of anthracycline drugs on HER2-positive breast cancer may be affectd by the synergistic amplification of the TOP2A gene (19). The TOP2A gene is adjacent to the hER2 gene, located in the 21 site of the long arm of chromosome 17, which is expressed as amplification or deletion in breast cancer with HER2 gene amplification.…”
Section: Discussionmentioning
confidence: 99%
“…One major way of defining the type of breast cancer is whether or not it is endocrine receptor (estrogen or progesterone receptor)-positive, HER2-positive, triple-negative (not positive to receptors for estrogen, progesterone or HER2) or triple-positive (positive for estrogen receptors, progesterone receptors and HER2) (7,8). These classifications provide oncologists with valuable information about how the tumor acts and what type of treatments may work best.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, according to the new St. Gallen consensus recommendations, Ki67 is one of the prognostic markers that is considered important to subclassify luminal A and luminal B, together with HER2 expression (12). The absence of ER, PR and HER2 is used to define the triple-negative subtype, which represents ~15% of breast tumours and is not a homogeneous entity (13)(14)(15). Thus, new prognostic and/or predictive factors may provide additional risk stratifications to better guide treatment decisions in these different subtypes of breast cancer.…”
Section: Introductionmentioning
confidence: 99%